Treatment processes and demographic variables as predictors of dropout from trauma-focused cognitive behavioral therapy (TF-CBT) for youth. (August 2018) - Yasinski, Carly; Hayes, Adele M.; Alpert, Elizabeth; McCauley, Thomas; Ready, C. Beth; Webb, Charles; Deblinger, Esther
Abstract: Objective: Premature dropout is a significant concern in trauma-focused psychotherapy for youth. Previous studies have primarily examined pre-treatment demographic and symptom-related predictors of dropout, but few consistent findings have been reported. The current study examined demographic, symptom, and in-session process variables as predictors of dropout from Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) for youth. Method: Participants were a diverse sample of Medicaid-eligible youth (ages 7–17; n = 108) and their nonoffending caregivers ( n  = 86), who received TF-CBT through an effectiveness study in a community setting. In-session process variables were coded from audio-recorded sessions, and these and pre-treatment demographic variables and symptom levels were examined as predictors of dropout prior to receiving an adequate dose of TF-CBT (<7 sessions). Twenty-nine children were classified as dropouts and 79 as completers. Results: Binary logistic regression analyses revealed that higher levels of child and caregiver avoidance expressed during early sessions, as well as greater relationship difficulties between the child and therapist, predicted dropout. Those children who were in foster care during treatment were less likely to drop out than children living with parents or relatives. No other demographic or symptom-related factors predicted dropout. Conclusions: These findings highlight the importance of addressing avoidance and therapeutic relationship difficulties in early sessions of TF-CBT to help reduce dropout, and they have implications for improving efforts to disseminate evidence-based trauma-focused treatments. Highlights: Predictors of dropout from TF-CBT for youth were examined. In-session child avoidance and therapeutic relationship problems predicted dropout. In-session caregiver avoidance predicted dropout. Being in foster care, but no other baseline variables, predicted retention. Therapists should attend to avoidance and relationship factors to prevent dropout.